Highly sensitive CE-ESI-MS analysis of N-glycans from complex biological samples - Guinevere S. M. Lageveen-Kammeijer (Nature Portfolio, 2019)
In-depth characterization of complex glycomes is complicated by the immense structural diversity of glycans. Here, the authors present a mass spectrometry-based strategy for untargeted, sensitive glycan profiling and identify 167 N-glycan compositions in total human plasma.